Reframing Pancasila Learning as Public Service Delivery: Evidence from Student-Oriented Higher Education Governance at Pontianak State Polytechnic - Mujib Mujib; Kasdi Tri Aryada; Mery Lestari; Farida Asy’ari; Tri Meliana (Public Policy and Management Inquiry, 2026)
The transformation of higher education governance in Indonesia requires universities to deliver student-centred educational services that emphasise both academic excellence and meaningful learning experiences. Pancasila courses, as part of the compulsory national curriculum mandated in Indonesian higher education, play a strategic role in fostering civic values, national identity, and character development while simultaneously functioning as educational public services. However, empirical studies examining the quality of Pancasila learning services from a higher education governance perspective remain limited, particularly in vocational higher education institutions. This study aims to analyse the quality of Pancasila learning services at Pontianak State Polytechnic from students' perspectives. This study employed a quantitative, descriptive research design with 80 students from eight academic departments, selected through proportional representation. Data were collected through a SERVQUAL-based questionnaire encompassing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Descriptive statistical analysis was utilised to interpret students' perceptions of learning service quality. The findings show that students perceive the overall quality of Pancasila learning services positively, identifying empathy as the most prominent dimension, followed by responsiveness, assurance, reliability, and tangibles. The findings show that relational dimensions, especially lecturer-student interaction, responsiveness, and sympathetic engagement, contribute more considerably to perceived service quality than physical facilities. These outcomes support the perspective that educational service quality is co-produced through the interactions between lecturers, as service providers, and students, as active service users. This study adds to public management theory by repositioning Pancasila learning from a traditional knowledge-transmission model toward a student-oriented educational paradigm for public service delivery. From a governance perspective, the findings highlight the need for higher education institutions to strengthen accountability, responsiveness, student participation mechanisms, and continuous quality assurance systems, as part of broader higher education governance reforms. The study shows that Pancasila education should be viewed not solely as a regulatory obligation but as a strategic instrument to advance student-oriented governance and improve public service performance in vocational higher education institutions.